2021
DOI: 10.3389/fgene.2020.560997
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer Analysis of Head-to-Head Gene Pairs in Terms of Transcriptional Activity, Co-expression and Regulation

Abstract: BackgroundHead-to-Head (H2H) gene pairs are regulated by bidirectional promoters and divergently transcribed from opposite DNA strands with transcription start sites (TSSs) separated within 1 kb. H2H organization is ancient and conserved, and H2H pairs tend to exhibit similar expression patterns. Although some H2H genes have been reported to be associated with disease and cancer, there is a lack of systematic studies on H2H organization in the scenario of cancer development.MethodsHuman H2H gene pairs were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
(59 reference statements)
1
8
0
Order By: Relevance
“…1646 protein coding H2H genes were identified, selecting genes which are on opposite strands to avoid counting adjacent gene pairs. This updated list of protein coding H2H gene pairs is a 38% increase from the most recent pan-cancer analysis of H2H pairs, which identified 1196 protein coding pairs (Chen et al ., 2021). Updates to genome annotation databases and TSS data can account for this increase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1646 protein coding H2H genes were identified, selecting genes which are on opposite strands to avoid counting adjacent gene pairs. This updated list of protein coding H2H gene pairs is a 38% increase from the most recent pan-cancer analysis of H2H pairs, which identified 1196 protein coding pairs (Chen et al ., 2021). Updates to genome annotation databases and TSS data can account for this increase.…”
Section: Resultsmentioning
confidence: 99%
“…As previous pan-cancer analyses of H2H genes have revealed that gene pairs have significantly altered co-expression matrices, it is quite possible that unique biomarkers could be found among differentially co-expressed H2H pairs (Chen et al ., 2021). H2H genes involving DNA repair and carcinogenesis genes being differentially co-expressed is also rather common, disrupting the expression coordination of these crucial genes.…”
Section: Introductionmentioning
confidence: 99%
“…Genes for both DNA repair systems and mitochondrial respiration can be classified as H2H genes, which are regulated by bidirectional promoters. 25 Interestingly, 43% of DR genes are classified as H2H genes with another gene located on the opposite strand within 1 kb upstream from the TSS ( Figure 5B ). H2H pairs tend to show similar expression patterns because of the shared promoter activity, but DR H2H pairs showed divergent gene expression after dTAG-13 treatment ( Figures 5C and 5D ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a synchronized regulation for these genes could be important for cell division with continuous cell cycling. 25 , 27 The pause release of RNAPII also has an important role in synchronous patterns of gene activation. 42 The evolution of the pause release system in H2H genes might have coincided with the molecular evolutions of the SETD1A-NELF axis to enable more precise and synchronized gene regulation in vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…We used the RNA-seq HTSeq count dataset of 22 cancer and paired normal samples from TCGA. A pan-cancer analysis of head-to-head gene pairs [ 100 ] reported that these gene pairs show significantly stronger positive correlations in tumor compared to normal samples, regardless of tumor types. Moreover, bidirectional promoters are known to regulate the expression of many cancer-related genes such as BRCA1 and TP53 [ 101 , 102 ].…”
Section: Resultsmentioning
confidence: 99%